The Influence of Employee Discipline and Perceived Organizational Support on Organizational Commitment among Employees in the Population and Civil Registry Office Surabaya - Anjesaya Melias Banta Sebayang; Endang Iryanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the influence of employee discipline and perceived organizational support (POS) on organizational commitment among civil registry employees in Surabaya. Data were gathered from 50 public servants through structured questionnaires, utilizing the Partial Least Squares (PLS) method. The findings reveal that both employee discipline and POS positively and significantly impact organizational commitment. These results emphasize the vital roles of organizational support and workplace discipline in nurturing employee loyalty and responsibility.